2019
DOI: 10.3847/1538-4357/ab4b43
|View full text |Cite
|
Sign up to set email alerts
|

UVIT Open Cluster Study. II. Detection of Extremely Low Mass White Dwarfs and Post–Mass Transfer Binaries in M67

Abstract: A detailed study of the ultraviolet (UV) bright stars in the old open star cluster, M67 is presented based on the far-UV observations using the Ultra Violet Imaging Telescope (UVIT) on ASTROSAT. The UV and UV-optical colour-magnitude diagrams (CMDs) along with overlaid isochrones are presented for the member stars, which include blue straggler stars (BSSs), triple systems, white dwarfs (WDs) and spectroscopic binaries (SB). The CMDs suggest the presence of excess UV flux in many members, which could be extrins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 83 publications
(163 reference statements)
3
66
0
Order By: Relevance
“…We have detected WD companions to BSSs in the OC M67 (Sindhu et al 2019(Sindhu et al . 2020Jadhav et al 2019), and in the outskirts of the GC NGC 5466 (Sahu et al 2019), using the UVIT images. Leiner et al (2019) identified a fast rotating MS star and suggested that it could be a post-MT product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have detected WD companions to BSSs in the OC M67 (Sindhu et al 2019(Sindhu et al . 2020Jadhav et al 2019), and in the outskirts of the GC NGC 5466 (Sahu et al 2019), using the UVIT images. Leiner et al (2019) identified a fast rotating MS star and suggested that it could be a post-MT product.…”
Section: Introductionmentioning
confidence: 99%
“…As this star is located on the MS, rather than the normal BSSs, which are brighter and bluer than the MS tip, they named it a blue-lurker (BL). Jadhav et al (2019), detected the presence of WD companions to two MS stars in M67, which can be classified as BLs. One has a confirmed post-MT nature, as its companion is a ELM WD.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet imaging of binary systems reveals the presence of hotter companions in the binary system, given that the hotter companion is luminous in UV. Old OCs such as NGC 188 and NGC 2682 are rich with BSSs, binary stars and contain many such optically sub-luminous UV-bright companions (Subramaniam et al 2016;Sindhu et al 2019;Jadhav et al 2019). Similar companions have been identified to BSSs in the outskirts of GCs (Sahu et al 2019;Singh et al 2020).…”
Section: Introductionmentioning
confidence: 75%
“…Otherwise, the secondary will be fainter than the MSTO and can be classified as a blue lurker. The blue lurkers are identified by their high stellar rotation (Leiner et al 2019) or evidence of extremely low-mass (ELM) white dwarf (WD) companion (Jadhav et al 2019). Depending on the evolutionary status of binary components, the binary system can be observed as main sequence (MS)?MS, contact binaries (Rucinski 1998), common envelop, MS?horizontal branch (HB;Subramaniam et al 2016), MS?extreme HB (EHB; Singh et al 2020), MS?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation